VIABILITAS BENIH NANGKA (Artocarpus heterophyllus Lmk.) PADA PELBAGAI STADIA KEMASAKAN DAN LETAK BIJI - Ainun Marliah (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2009)
Seed Viability of Jackfruit in Relation to Fruit Ripening Stadiums and Seed Position Ainun Marliah*, Said Imran, dan AlkausarFakultas Pertanian, Universitas Syiah kuala, Darusalam Banda Aceh ABSTRACT The aim of this research was to evaluate effect of fruit ripening stadiums, seed position inside the fruit, and interaction between them, on jack fruit seed viability. Units of research arranged according to completely randomized design (CRD) with 3 replicates. The factor of fruit ripening stadiums consisted of 3 levels: before, in and after physiological maturity, and also the factor of seed position inside the fruit consisted of 3 levels: both ends and at the middle of the fruit. Observations conducted to the potency to germinate, Germination capacity, rate of germination and uniformity of germination. The results showed that germination capacity, rate of germination and uniformity of germination were highly significant affected and potency to germinate was significantly effected by fruit ripening stadiums. The highest jackfruit seed viability was found from physiological matury stadium. Germination capacity and rate of germination also highly significantly affected by seeds position inside the fruit, but not significant on the potency to germinate and uniformity of germination. The highest jack fruit seeds vibility come from the middle of the fruit. There was a very significant of both factors on seed rate of germination, significant interaction on germination capacity, and not significant to other parameters.